Penguatan Pendekatan Ilmu Kesehatan Olahraga pada Alumni Pendidikan Kepelatihan Olahraga - Moch. Yunus; Prisca Widiawati; Alifia Candra Puriastuti; Muhammad Putra Ramadhan; Purwadi, Dinda Arisetya; Ulma Erdilanita (Universitas Muhammadiyah Malang, 2024)
Purpose – The purpose of this service is to facilitate sports coaching education alumni to hone quality and add insight into sports coaching in the field of sport medicine (sports health) so that they can analyze the health status of athletes in carrying out a given training program, can find out the design of exercises that are suitable for the growth and development of athletes, and handling post-injury athletes. Design/methodology/approach – In this service activity using the lecture method by conveying material about sports health, practicing material that has been obtained from resource persons, providing implementation support by conducting implementation assistance, measuring results through comparison of pre-test and post-test scores given, and following up on results by analyzing the data obtained from the results of the pre-test and post-test. Findings – From this community service activity, the results of the pre-test data analysis showed a percentage of 50.5%, after being converted using the criteria table, it can be concluded that the results of the pre-test data are included in the fairly effective category. While the analysis of the post-test data shows a percentage of 81.33%, after being converted using the criteria table, it can be concluded that the results of the post-test data are included in the very effective category. This shows that there is an increase in knowledge of alumni after the implementation of sports health hybrid training and being given products in the form of videos on sports health material. The video can be used as a guide or literature reference by sports coaching education alumni when they are in the field to manage the health and nutrition of athletes and students. Originality/value – Previous articles were limited to delivering exercise physiology material. Therefore, the community service team carries out strengthening the sports health science approach which includes nutrition and sports material, sports injury first aid, splint dressing, and physical activity in children which is carried out in a hybrid manner. The results of the dedication of the team proposing this activity are expected to produce professional trainers who are ready to compete in the world of sports coaching.